Hubungan Health Locus of Control dengan Kepatuhan Minum Obat Pasien Hipertensi di Puskesmas Sidorejo Kota Pagaralam - Yayu Anggriani; Dini Rudini; Yosi Oktarina (Malahayati Nursing Journal, 2024)
ABSTRACT Hypertension is a condition where blood pressure increases relentlessly. Pharmacological treatment is the primary management of hypertension to control blood pressure and prevent complications. Adherence to taking medication is necessary for the goal to be achieved, but a number of studies have found that adherence to treatment is still low. The purpose of this study was to determine the relationship between health locus of control and adherence to taking medication for hypertensive patients at Sidorejo Health Center in Pagaralam city. This study used quantitative methods and a cross sectional approach with a population of 428 people and 90 samples calculated using the Yamane formula. The sampling technique was consecutive sampling. The measuring instruments used were multidimensional health locus of control scales and morisky medical adherence scale-8 items with univariate data analysis in the form of frequency distribution and bivariate with Spearman Rank test. This research was conducted at Sidorejo Health Center in Pagaralam city. The results of this study obtained hypertensive patients with high health locus of control 41 people (45.6%) and low 49 people (54.4%). While the level of compliance with taking medication is high 20 people (22.2%), moderate 25 people (27.8%) and low 45 people (50%). The results of the Spearman Rank statistical test obtained a p value = 0.000 (p 0.05) and r = 0.671, meaning that there is a positive and strong relationship between health locus of control and compliance with taking medication for hypertensive patients at the Sidorejo Health Center in Pagaralam city. Health locus of control and compliance with taking medication in hypertensive patients is still relatively low. Health locus of control has a strong relationship and affects adherence to taking medication for hypertensive patients, it is hoped that this research can be an evaluation and policy basis as well as a source of reading for Sidorejo Health Center, Education and Nursing Profession and further researchers. Keywords: Health Locus of Control, Medication Adherence, Hypertension  ABSTRAK Hipertensi merupakan keadaan dimana tekanan darah meningkat tanpa henti. Pengobatan farmakologis merupakan penatalaksanaan utama hipertensi guna untuk mengontrol tekanan darah dan mencegah komplikasi. Kepatuhan minum obat diperlukan agar tujuan tercapai, namun sejumlah penelitian menemukan kepatuhan terhadap pengobatan masih rendah. Tujuan penelitian ini adalah untuk mengetahui hubungan health locus of control dengan kepatuhan minum obat pasien hipertensi di Puskesmas Sidorejo kota Pagaralam. Penelitian ini menggunakan metode kuantitatif dan pendekatan cross sectional dengan populasi sebanyak 428 orang dan 90 orang sampel yang dihitung menggunakan rumus Yamane. Teknik pengambilan sampel ialah consecutive sampling. Alat ukur yang digunakan adalah multidimensional health locus of control scales dan morisky medical adherence scale-8 items dengan analisa data univariat berupa distribusi frekuensi dan bivariat dengan uji Spearman Rank. Penelitian ini dilakukan di Puskesmas Sidorejo kota Pagaralam. Hasil penelitian ini didapatkan pasien hipertensi dengan health locus of control tinggi 41 orang (45,6%) dan rendah 49 orang (54,4%). Sedangkan tingkat kepatuhan minum obat tinggi 20 orang (22,2%), sedang 25 orang (27,8%) dan rendah 45 orang (50%). Hasil uji statistik Spearman Rank didapatkan nilai p value=0,000 (p0,05) dan r=0,671, artinya terdapat hubungan positif dan kuat antara health locus of control dengan kepatuhan minum obat pasien hipertensi di Puskesmas Sidorejo kota Pagaralam.Health locus of control dan kepatuhan minum obat pada pasien hipertensi masih tergolong rendah. Health locus of control mempunyai hubungan yang kuat dan mempengaruhi kepatuhan minum obat pasien hipertensi, diharapkan penelitian ini dapat menjadi evaluasi dan dasar kebijakan serta sumber bacaan bagi Puskesmas Sidorejo, Pendidikan dan Profesi Keperawatan serta Peneliti selanjutnya. Kata Kunci: Health Locus of Control, Kepatuhan Minum Obat, Hipertensi